Relationship between DAPI-fluorescence fading and nuclear DNA content: An alternative method to DNA quantification? - CRISTIAN GALLARDO-ESCÁRATE; JOSUÉ ÁLVAREZ-BORREGO; ELISABETH VON BRAND; ENRIQUE DUPRÉ; MIGUEL ÁNGEL DEL RÍO-PORTILLA (Biological Research, 2007)
In observations by confocal or conventional fluorescence microscopy, important factors should be considered in order to obtain accurate images. One of them, such as the fluorescence bleaching from highest intensity to lowest signal of fluorescence is a common problem with several DNA fluorochromes and especially for DAPI stain. The fluorescence of DAPI fades rapidly when it is exposed to UV light, under optimal conditions of observation. Although the fading process can be retarded using a mounting medium with antifading reagents, the photochemical process underlying the fluorescence decay has not yet been fully explained. In addition, no relationship between fluorescence fading and nuclear DNA content has been tested. In order to test this relationship, we measured by means of image analysis the DAPI-fluorescence intensity in several cellular types (spermatozoa, erythrocytes and haemocytes) during their fluorescence bleaching. An algorithm specifically built in MATLAB software was used for this approach. The correlation coefficient between nuclear DNA content and DAPI-fluorescence fading was found equal to 99%. This study demonstrates the feasibility to measure nuclear DNA content by fluorescence fading quantification, as an alternative method concurrently with image analysis procedures